Performance of Buyout IPO’s as compared to Non Buyout IPO’s in the UK - TALREJA, KARISHMA (2009)
Purpose – The aim of the paper is to compare the performance of buyout firms to non buyout firms of UK, post the initial public offerings (IPOs). The aim is achieved by examining the post IPO financial performance of the two groups by analyzing the absolute accounting statistics. The results from analyzing the accounting data is further confirmed then, with the testing of the cash flow statics that are less prone to accounting manipulation with the Mann Whitney U test.